Some results on vector bundle monomorphisms - Goncalves, Daciberg L.; Libardi, Alice K. M. [UNESP]; Neto, Oziride Manzou (Geometry & Topology Publications, 2007)
In this paper we use the singularity method of Koschorke [2] to study the question of how many different nonstable homotopy classes of monomorphisms of vector bundles lie in a stable class and the percentage of stable monomorphisms which are not homotopic to stabilized nonstable monomorphisms. Particular attention is paid to tangent vector fields. This work complements some results of Koschorke [3; 4], Libardi-Rossini [7] and Libardi-do Nascimento-Rossini [6].